Cryopreservation of Crassostrea gigas vesicular cells: Viability and metabolic activity - Hanquet, Anne-caroline; Kellner, K; Heude, C; Naimi, Amine; Mathieu, M; Poncet, J.m. (Cryobiology, 2006)
Cryopreservation is widely used for long-term conservation of various tissues, embryos or gametes. However, few studies have described cryopreservation of invertebrate primary cell cultures and more particularly of marine invertebrate somatic cells. This technique would however be of great interest to facilitate the study of various metabolic processes which vary seasonally. The aim of the present study was to develop a protocol for cryopreservation of Crassostrea gigas vesicular cells. Different parameters were adjusted to improve recovery of cells after freezing. The most efficient cryoprotectant agent was a mix of Me2SO, glycerol, and ethylene glycol (4% each). The optimal cooling rate was -1 degrees C min(-1) down to -70 degrees C before transfer into liquid nitrogen. In these conditions the percentage of viable cells reached 70% of the control. The glucose metabolism of thawed cells was evaluated using radioactive glucose as a tracer. Immediately after thawing, glucose uptake involving membrane transporters was greatly reduced (24% of control) whereas glucose incorporation into glycogen was less affected (68% of control). (c) 2006 Elsevier Inc. All rights reserved.